Approaching the Miocene Climatic Optimum in Patagonia (Southern Argentina): Temperature Seasonality and a Potential Role for the Opening Drake Passage - Ivany, Linda C. (2025)
The Miocene Epoch (23.03–5.33 Ma) is receiving increased attention because estimated pCO2 andits associated warmth is comparable to projections over the next century. Well‐constrained sea‐surface temperatures in the tropics and northern latitudes express amplified warming during the Miocene Climatic Optimum (MCO; 16.9–14.7 Ma), yet data from the Southern hemisphere are few, especially in the mid‐high south Atlantic, and proxies appear to suggest only moderate warming. Here, we present seasonally resolved oxygen isotope data from fossil marine bivalves in the Early Miocene (Burdigalian) Monte León Formation of southern Patagonia, Argentina, and explore their implications for Miocene paleoclimate. Paleoclimate simulations from the Miocene isotope enabled Earth System Model (iCESM1.2) allow for proxy‐model comparison. Mean annual paleotemperatures increase from∼15°C to ∼20°C between ∼19.3–17.5 Ma, consistent with model predictions at400 and 560 ppm CO2, respectively. Using a recently reported isotopically positive ocean, calculatedpaleotemperatures are 4°C warmer still, more akin to the warmth documented in the early‐mid Miocene northern hemisphere. Both reinforce mid‐high‐latitude warmth in the approach to the MCO, but the second well exceeds model‐predicted temperatures, even at higher pCO2. Seasonal range increases upsection from∼3.5°C to ∼6.4°C, with more warming in the summer, potentially reflecting an increase in the influence of a seasonally oscillating Malvinas current on the Patagonian coast associated with an increasingly open Drake Passage. The fact that paleoSSTs are substantially warmer than those in the study area today (6–10°C), despite only moderately elevatedestimated pCO2, merits further attention.